Effects of progressive versus consistent dose of caffeine ingestion on volleyball players’ exercise performance adaptations following plyometric jump training - Zhu, Ganfang; Fu, Keqi; Xie, Yangzheng (Frontiers in Nutrition, 2025)
BackgroundThe consumption of caffeine (CAF) to enhance adaptations in athletes has been documented in prior studies; however, the identification of an optimal approach for CAF supplementation during short-term interventions remains unclear. This study aimed to investigate how different caffeine (CAF) dosage strategies consumed 1 h before plyometric jump training (PJT) affect exercise performance adaptations in male volleyball athletes.MethodsA total of thirty-two young volleyball players volunteered for the study and were randomly divided into four groups: 3 mg/kg of caffeine (CAF-3, n = 8), 6 mg/kg of caffeine (CAF-6, n = 8), progressively increases from 3 to 6 mg/kg of caffeine (CAF-3 to 6, n = 8), and placebo (PL, n = 8). All athletes engaged in a 4-week PJT intervention, three times a week, and ingested their CAF or PL in a double-blind manner 1 hour prior to the PJT sessions. Countermovement vertical jump (CMVJ), spike jump (SPJ), block jump (BLJ), 10-m sprint, T-test change of direction speed (T-CODS), maximal strength, and Wingate anaerobic power test were assessed both before and after the training intervention.ResultsThe CAF-3 to 6 and CAF-6 groups showed more gains (p < 0.05) than the CAF-3 and PL groups in the CMVJ (7.6 and 6.9% vs. 4.3 and 4.1%), SPJ (2.5 and 2.3% vs. 1.4 and 1.4%), BLJ (1.1 and 1.0% vs. 0.7 and 0.7%), 10-m sprint (−7.5% and −7.4% vs. −5.2% and −5.0%), T-CODS (−5.4% and −5.2% vs. −3.8% and −3.5%), 1RM strength (5.2 and 5.3% vs. 2.5 and 2.4%), peak power (10.1 and 9.4% vs. 6.2 and 6.0%) and mean power (8.7 and 8.2% vs. 5.1 and 4.9%), respectively, following the training period. However, no significant (p > 0.05) differences were observed between the CAF-3 to 6 versus CAF-6 in the magnitude of adaptations in the performance of players after training period.ConclusionIn summary, elevated caffeine intake serves as an ergogenic aid to enhance exercise performance adaptations in volleyball athletes. Furthermore, a progressive CAF loading strategy appears to be as effective as maintaining a consistent dosage throughout a 4-week PJT program. This approach presents a viable option for CAF supplementation, potentially attenuating total CAF usage while eliciting similar training benefits.